Agrivoltaic systems for sustainability: An overview of emerging trends and practices - Maity, Rittick; Hariram, N. P.; Quazi, M. M.; Sudhakar, K. (Elsevier Ltd, 2025)
Agrivoltaics, the concurrent use of land to produce energy and grow crops, represents a form of sustainable land management. The paper critically reviews the integration of solar energy with land used for agriculture, grazing, aquatic environment, and wildlife conservation. These integrations offer a dual advantage, lowering heat stress to ensure their survival and boosting agricultural produce and energy generation. The research specifically reviews to evaluate the benefits of agrivoltaics, such as increased land efficiency, improved crop yields, and enhanced livestock welfare, while addressing associated challenges like ecological impacts and technical constraints. The purpose of the research is to give an overview of integrated systems with agrivoltaics, including their benefits, challenges, and potential applications. This research focuses on developing sustainable, resilient, and multifunctional land-use systems by defining and optimising synergies between solar energy and various agricultural practices.